Cytokine expression in cord blood cells of children of healthy and allergic mothers - Hrdý, J; Zanvit, P; Novotná, O; Kocourková, I; Zižka, J; Prokešová, L (Folia microbiologica, 2010)
To determine some early signs connected with the increased risk of future allergy development, gene expression and production of selected cytokines were tested in children of allergic mothers and compared with newborns of healthy mothers. Expression of IL-1β, IL-2, IL-4, IL-8, IL-10, IL-13, IFN-γ, TNF-α, TGF-β and EGF was tested in cord blood cells using real-time PCR and production of these cytokines was evaluated in cord sera by ELISA. Gene expression of IL-2, IL-4, IL-8, IFN-γ, IL-1β, TNF-α and TGF-β was decreased and that of IL-10, IL-13 and EGF increased in children of allergic mothers in comparison with those of healthy mothers. Significant differences in sera of healthy and allergic groups were only in IL-10 and EGF. Different relationship among serum cytokine levels reflects the fact that the cytokines are not produced only by blood cells. Significantly decreased production of EGF in newborns of allergic mothers could negatively influence maturation of mucosal membranes of these children and support thus their easier allergization. Allergic phenotype pointing to the bias to T(H)2 response and to possibly impaired intestine maturation was apparent already on the level of cord blood and could serve as a predictive sign of increased allergy risk.
Keywords: exprese genu; Gene Expression; interleukin-10; cytokiny; Pregnancy; těhotenství; Epidermal Growth Factor; polymerázová řetězová reakce s reverzní transkripcí; Interleukin-10; ELISA; alergie; fetální krev; Fetal Blood; novorozenec; Enzyme-Linked Immunosorbent Assay; lidé; ženské pohlaví; Humans; Infant, Newborn; Reverse Transcriptase Polymerase Chain Reaction; Cytokines; Female; Hypersensitivity; epidermální růstový faktor